2010
DOI: 10.2146/ajhp100096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of International Normalized Ratios provided by two point-of-care devices and laboratory-based venipuncture in a pharmacist-managed anticoagulation clinic

Abstract: INR measurements generated by POC devices exhibited positive bias, compared with laboratory-based venipuncture, for INR values at the high end of the INR range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…5 Williams et al published a study in 2007, based on 97 INR samples from patients in a pediatric age group, in which 13% of cases would have been treated differently if the Coaguchek XS device had been used and reported that 19% of the samples had variation greater than 0.5 INR points. The study also compared the device with its predecessor (Coaguchek S), observing that it offered greater efficacy and recommending substitution.6 food and medicines.…”
Section: Discussionmentioning
confidence: 99%
“…5 Williams et al published a study in 2007, based on 97 INR samples from patients in a pediatric age group, in which 13% of cases would have been treated differently if the Coaguchek XS device had been used and reported that 19% of the samples had variation greater than 0.5 INR points. The study also compared the device with its predecessor (Coaguchek S), observing that it offered greater efficacy and recommending substitution.6 food and medicines.…”
Section: Discussionmentioning
confidence: 99%
“…27 Additional studies have demonstrated a wide range of differences between POC and standard results as well as variability among POC devices, which introduces concern regarding the reliability and reproducibility of POC results. 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…However, discrepancies between INRs determined by POC-instruments and laboratory measurements are reported (9,10,23) , and the discrepancies may have clinical impact (6,28) . It is therefore important that the causes of these differences are understood.…”
Section: Discussionmentioning
confidence: 99%
“…POC instruments are calibrated by the manufacturer and the precision and accuracy for some of the instruments have been examined (5 -7) . The performance of the newest POC instruments has improved (8) , although there are still challenges (9) , especially at the high end of the INR range (10) .…”
Section: Introductionmentioning
confidence: 99%